PERBAIKAN SISTEM PENGGAJIAN APOTEK X DI BANDAR LAMPUNG DENGAN METODE POINT SYSTEM (ADHERED) - Mutiara Islammya Roskar Atmojo; Cindy Nuraeni Sutisna; Silvy Mutiara; Muhammad Dyaz Tri Nurminda; Jenny Mulyani (KOLEGIAL, 2022)
The importance of compensation for employees as individuals is that the magnitude of the compensation reflects the value of their work among the employees themselves, family, and community. Compensation is all the income that comes in the form of money, direct or indirect goods that employees receive in return for services rendered to the company. The object of this journal study is the Apotek X which is one of the pharmacies located in Bandar Lampung city. The study was done to analyze and implement an effective and fair evaluation of the compensation system of the Apotek X among the 2 methods of adhered and overlapping. The data used in this study are primary data. Primary data collection technique consists of electronic media interviews which are zoom and whatsapp as questionnaires. The study is a quantitative and qualitative study by describing the compensation system used in the pharmacy of Apotek X.